Use of Allopurinol in Slowing the Progress of Chronic Kidney Disease Stage III and IV (Bangladesh Journal of Medicine, 2021)
Background: Hyperuricemia is associated with the event of hypertension and renal disease progression. The aim of the study was to evaluate the role of allopurinol in slowing the progression of chronic kidney disease (CKD) stage III and IV.Methods: This study was prospective interventional study was carried out in department of Nephrology, Sir Salimullah Medical College and Mitford Hospital, Dhaka, during the period of January 2014 to December 2014. On the basis of inclusion and exclusion criteria a total of 80CKD patients were enrolled in this study.80 patients were distributed in two groups. 40 patients were placed in treatment group and 40 patients were placed in control group. Purposive sampling method was followed.40 patients of treatment group were administered allopurinol 100 mg daily. Clinical, hematologic, and biochemical parameters were measured at baseline, at 4th month and 8th month of treatment.Results: No significant differences were seen between baseline SBP, DBP, Hb and HbA1c with 4th month and 8th follow up in both treatment group and control group. eGFR was significantly less declined at 4th months and 8thmonths in patient treated with allopurinol (treatment group). A negative Pearson’s correlation (r= -0.104; p=0.524) was found between uric acid with eGFR at 8th month in treatment group and significant positive Pearson’s correlation (r= 0.559 p=0.001) was found with CRP level. eGFR was significantly more declined at 4th months and 8th months in patient of control group. In control group a negative Pearson’s correlation (r= -0.126 p=0.437) was found between uric acid with eGFR at 8th month and positive Pearson’s correlation (r= 0.275 p=0193) was found with CRP level.Conclusions: Uric acid and CRP were significantly declined at 8th months in treatment group. Thus eGFR progression was significantly slow in treatment group at 4thmonths and 8th months from baseline due to positive effect of allopurinol by reducing inflammatory process that causes by high uric acid.Bangladesh J Medicine July 2021; 32(2) : 85-89